2019
DOI: 10.1111/hae.13763
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Nuwiq®(simoctocog alfa) activity using one‐stage and chromogenic assays—Results from an international comparative field study

Abstract: Background Accurate determination of coagulation factor VIII activity (FVIII:C) is essential for effective and safe FVIII replacement therapy. FVIII:C can be measured by one‐stage and chromogenic substrate assays (OSAs and CSAs, respectively); however, there is significant interlaboratory and interassay variability. Aims This international comparative field study characterized the behaviour of OSAs and CSAs used in routine laboratory practice to measure the activity of Nuwiq® (human‐cl rhFVIII, simoctocog alfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 32 publications
(79 reference statements)
2
7
0
1
Order By: Relevance
“…Even if slight differences were noted for mean FVIII recovery measured by one-stage clotting assay at visit 1 between children and adults (all products-combined; p = 0.0003; 1.95, 1.76, 1.8 respectively at visit 1, 2, 3 for children; 2.61, 2.40, 2.40 respectively at visit 1, 2, 3 for adults) as well as between Nuwiq® and Zonovate® (p = 0.0042; 2.09, 1.74, 1.9 respectively at visit 1, 2, 3 for Nuwiq®; 2.65, 2.38, 2.38 respectively at visit 1, 2, 3 for Zonovate®), all values were still comparable to previous reports, [4][5][6][7] considering that 49.6% of our subjects were obese (20.1%) or overweight (29.5%) 8,9 and that 73% of the children in our cohort were switched to Nuwiq®. 7 As previously observed in clinical trials for Nuwiq® and Zonovate® in previously treated PWHA, [10][11][12][13] no inhibitors were detected upon study entry by Nijmegen-modified Bethesda (NBA) assay or enzyme-linked immunosorbent assay (ELISA; used as a complementary approach to detect both neutralizing and non-neutralizing antibodies) even in the 3 subjects with less than 50 ED.…”
Section: E T T E R T O T H E E D I T O R Evaluation Of Anti-factor Viii Antibodies In Haemophilia a Subjects Switching Products Followingsupporting
confidence: 89%
“…Even if slight differences were noted for mean FVIII recovery measured by one-stage clotting assay at visit 1 between children and adults (all products-combined; p = 0.0003; 1.95, 1.76, 1.8 respectively at visit 1, 2, 3 for children; 2.61, 2.40, 2.40 respectively at visit 1, 2, 3 for adults) as well as between Nuwiq® and Zonovate® (p = 0.0042; 2.09, 1.74, 1.9 respectively at visit 1, 2, 3 for Nuwiq®; 2.65, 2.38, 2.38 respectively at visit 1, 2, 3 for Zonovate®), all values were still comparable to previous reports, [4][5][6][7] considering that 49.6% of our subjects were obese (20.1%) or overweight (29.5%) 8,9 and that 73% of the children in our cohort were switched to Nuwiq®. 7 As previously observed in clinical trials for Nuwiq® and Zonovate® in previously treated PWHA, [10][11][12][13] no inhibitors were detected upon study entry by Nijmegen-modified Bethesda (NBA) assay or enzyme-linked immunosorbent assay (ELISA; used as a complementary approach to detect both neutralizing and non-neutralizing antibodies) even in the 3 subjects with less than 50 ED.…”
Section: E T T E R T O T H E E D I T O R Evaluation Of Anti-factor Viii Antibodies In Haemophilia a Subjects Switching Products Followingsupporting
confidence: 89%
“…Generalized product‐by‐product–based guidance about systematic under‐ or overestimation of activity for many reagent combinations is needed. Field studies for many new products, and in Europe UK NEQAS and ECAT quality control programs have also been performed and provided valuable information for the coagulation laboratories 13‐16 . For both Nuwiq and Elocta, field studies indicate that both OSA and CSA can be used for monitoring.…”
Section: Resultsmentioning
confidence: 99%
“…The authors concluded that Nuwiq can be measured with both one-stage and chromogenic assays without the need for a product specific standard. 29 Recommendations for monitoring Nuwiq 1. We recommend that one-stage and chromogenic FVIII assays calibrated with plasma standards can be used for monitoring…”
Section: Refacto Afmentioning
confidence: 99%
“…There were only minor differences between results obtained with different reagents. The authors concluded that Nuwiq can be measured with both one‐stage and chromogenic assays without the need for a product specific standard …”
Section: Factor VIII Productsmentioning
confidence: 99%